Analisis Determinasi Kemiskinan Di Provinsi Maluku Periode 2019–2023 : Pendekatan Regresi Data Panel - Haidar Akhmad Al Barabasi; Hastarini Dwi Atmanti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of Gross Regional Domestic Product (PDRB), Human Development Index (IPM), and Unemployment Rate on poverty levels in Maluku Province during the 2019-2023 period. A panel data regression approach was employed, allowing a comprehensive analysis by combining cross-sectional and time-series data. The results show that PDRB has a positive effect on poverty, while IPM has a significant negative effect, indicating that improvements in quality of life can reduce poverty. In contrast, the unemployment rate does not show a significant effect on poverty. Overall, the regression model used has a high explanatory power, with an R-squared of 0.952. This study contributes significantly to understanding the factors influencing poverty in island regions and provides insights for formulating more effective development policies in Maluku Province.